Child Socio-Emotional Skills: The Role of Parental Inputs - Gloria Moroni; Cheti Nicoletti; Emma Tominey (Institute of Labor Economics (IZA), 2019)
Informed by the psychological literature and our empirical evidence we provide new insights into the technology of socio-emotional skill formation in middle childhood. In line with economic evidence, increasing parental inputs that enrich the child home environment and reduce stress has larger returns for children with higher socio-emotional skills in early childhood (complementarity), but only for levels of inputs that are high. For low levels of inputs, i.e. levels implying a stressful home environment, an increase has a higher return for children with lower socio-emotional skills in early childhood (substitutability). Consequently, well targeted policies can reduce middle childhood socio-emotional gaps.
Keywords: J13; D10; I10; I31; 330; socio-emotional skills; complementarities; substitutabilities; parenting styles; mother's mental health; time investment; child behavioural disorders; diathesis-stress hypothesis